2018
DOI: 10.1002/gcc.22525
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation inactivate tumor suppressor FAM134B and is associated with poor prognosis in colorectal cancer

Abstract: The present study aims to examine promoter methylation status of FAM134B in a large cohort of patients with colorectal adenocarcinomas. The clinical significances and correlations of FAM134B promoter methylation with its expression are also analysed. Methylation-specific high-resolution melt-curve analysis followed by sequencing was used to identify FAM134B promoter methylation in colorectal adenomas (N = 32), colorectal adenocarcinomas (N = 164), matched adjacent non-neoplastic colorectal mucosae (N = 83) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…25). In colorectal cancer, FAM134B functions as a tumor suppressor gene (26), whereas in isocitrate dehydrogenase-mutant gliomas, FAM134B has been identified as a synthetic lethal target (27). These findings reinforce the context-dependent role for selective autophagy programs in cancer.…”
Section: Bulk Degradation and Selective Autophagy Can Both Affect Thementioning
confidence: 71%
“…25). In colorectal cancer, FAM134B functions as a tumor suppressor gene (26), whereas in isocitrate dehydrogenase-mutant gliomas, FAM134B has been identified as a synthetic lethal target (27). These findings reinforce the context-dependent role for selective autophagy programs in cancer.…”
Section: Bulk Degradation and Selective Autophagy Can Both Affect Thementioning
confidence: 71%
“…Inhibition of RETREG1 contributes to impaired proteostasis in the ER due to the accumulation of misfolded or aggregated proteins, leading to compromised neuronal survival and progressive neuronal degenerative diseases (26). In previous studies, RETREG1 was downregulated in colorectal cancer, and its low expression was associated with younger age, larger tumour size, advanced cancer stages, higher recurrence rate, lymphovascular invasion and poor prognosis of patients (27,28). Furthermore, overexpression of RETREG1 inhibited the proliferation of colorectal cancer cells in vitro, and tumour growth in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it was found that decreased FAM134B expression in colorectal adenocarcinomas is coupled with enhanced tumor aggressiveness, poor prognosis, and tumor re-occurrence as well as metastasis. Deeper analysis showed that in this type of cancer cells, FAM134B was inactivated through promoter methylation and interestingly this effect was found to be tumor stage—specific, i.e., late-stage cancer cells exhibited increased FAM134B promoter methylation in comparison to earlier ones (Islam et al, 2017 , 2018 ). Moreover, in colon cancer cells, an alternative FAM134B inhibition pathway through miR-186-5p, has been revealed rendering FAM134B a tumor suppressor, at least for this type of tumor (Kasem et al, 2014 ; Islam et al, 2017 ).…”
Section: Selective Autophagy Components In Cancermentioning
confidence: 99%